(untitled) (Ciudades, 2018)
On November 2003, the Italian Associazione Nazionale Centri Storico -artistici (ANCSA) and the Comune di Gubbio, awarded the "Regeneration of ’Pajarillos’ and ’Rondilla’ neighbourhoods of Valladolid (Spain)” study the dinstinctive Progetto segnalato in the european section of the Premio Gubbio 2003∗. The original document, “Estudio para la remodelación de los barrios de Pajarillos y Rondilla de Valladolid” was comisioned by the Sociedad municipal de suelo y vivienda de Valladolid S.A. tp a TBA made by the University Institute for Urban Research (IUU) of the University of Valladolid and the consulting company Inzamac-Tecoy. The works were started on December 1999 and finised on October 2002. On the part of the IUU, the writing team was formed by the following people: Juan Luis de las Rivas Sanz (director of IUU), Manuel Domingo Vaquero, Antonio Hoyuela Jayo (also member of Inzamac-Tecopy) and María A. Castrillo Romón. The main researcher was Alfonso Álvarez Mora and on the elaboration of the documents for the European Prize Gubbio 2003 collabored the following interns of the IUU: María Puente Antón, Javier Zanca Pernía and Rafael González Díez.